Temporary distribution of mollusks and tropical crustaceans in the Peruvian Province and its relation with the events El Niño - Paredes, Carlos (2004)
The incursion of 25 tropical species of mollusks and 15 of crustaceans have been analyzed. This species were registered among the years 1972 and 2003, time in which five El Niño events (EN) were occurred. Presence of the tropical species in the Peruvian Province would be related to larvae transport for benthonic species and juvenile for pelagic species, both stimulated by movements of the masses of waters. It is possible that some species have found «refuge areas» where to be developed and to remain, these species would display a discontinuous distribution in the Peruvian Province, like it is the case of Malea ringens, Prunum curtum and Bulla punctulata. Other species that intrude when typical oceanographic conditions of an event appear EN, apparently disappear when recovering the conditions «No Nino».